Hypertrophic cardiomyopathy: Affects and new therapies - Bakhodirova D. B. (Лучшие интеллектуальные исследования, 2024)
Hypertrophic cardiomyopathy (HCM) is one of the most common genetic heart diseases worldwide. It affects men and women equally and has been identified in persons of diverse ethnic backgrounds.1-7 HCM is characterized by a thickened, nondilated left ventricle and often causes exertional dyspnea and reduced exercise capacity, which can impair quality of life. Left ventricular outflow tract obstruction, which results from contact of the mitral valve with the ventricular septum during systole, is one of the principal determinants of HCM-related complications and therefore is an important target for therapy.Cardiac hyper contractility, which results from an excessive number of actin–myosin cross-bridges within the cardiac sarcomere, is an important mechanism that promotes outflow obstruction. Other factors include elongation of the mitral valve leaflets, apical displacement of the papillary muscles, and protrusion of the hypertrophied ventricular septum into the left ventricular outflow tract. This impedance to blood flow generates a left ventricular outflow tract pressure gradient, which can be reliably quantified with the use of echocardiography.